Optimization of solid‐state fermentation condition for crude protein enrichment of rice bran using Rhizopus oryzae in tray bioreactor - Andhika Cahaya Titisan Sukma; Herawati Oktavianty; Siswo Sumardiono (Universitas Gadjah Mada, 2021)
Enhancement of crude protein content in rice bran with the solid‐state fermentation method in tray bioreactor using Rhizopus oryzae FNCC 6011 has been investigated. This research aimed to optimize the fermentation condition using the response surface methodology (RSM). The central composite design (CCD) with three independent variables, including substrate thickness (1 to 3 cm), fermentation temperature (28 to 32 °C), and nutrient concentration of KH2PO4 (2 to 6 g/L) used to determine the crude protein enrichment. The quadratic model has successfully described the effect of variable interactions on responses very well as indicated by the F value and p‐value are 11.20 and 0.0041, respectively. The multiple correlation coefficients (R2) of 0.9438 indicated that 94.38% of the model data has approached the actual data with a deviation of 5.62%. The interaction between the variable substrate thickness and the fermentation temperature is the most influential variable on the crude protein enrichment of rice bran, indicated by the highest F value of 24.08 and the lowest p‐value of 0.0027. The highest protein increase of 62.51% was obtained at 2 cm substrate thickness, fermentation temperature of 30 °C, and KH2PO4 concentration of 4 g/L.